Gestión del recurso humano, estudio de caso “QUEVEXPORT S.A.” Cantón Quevedo 2015. - Morante Coello, Joice Maribel (2015)
This case study was implemented in the company QUEVEXPORT SA located at Km. 1 ½ Road to Valencia, in order to determine what the effect of administrative management unit Talent Company "Quevexport SA" on the job performance of employees and workers, research the following objectives: Diagnose the administrative management of Human Resource Unit in the company QUEVEXPORT SA Identify the factors that have influenced efficient and inefficient job performance of staff. Types of field research and literature in order to extract practice, actual information and theoretical information regarding the object of study were applied. The research methods were inductive and analytical methods that allowed analyzing the results will attain the objectives of the research. The survey technique applied to the entire study population, comprising a total of 32 employees was used. After the analysis and interpretation of the results it was concluded: the company has a functional organization and has defined the mission and vision; but not been socialized with their employees. There is no planning for human resource management, therefore no terms of personal reference is made either upon frugal recruitment. No regularly evaluates work performance, therefore the climate or the workplace are adequate, the same economic incentives accompanied by sporadic decreases motivation and commitment employer-employee, salvageable company with employees is given in training , job security and respect to the benefits of law; this is more negative than positive indices in identifying occupational factors which generates a degree of inefficiency in work performance were detected.